2015
DOI: 10.2337/dc15-1240
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Up Prolonged Sitting With Standing or Walking Attenuates the Postprandial Metabolic Response in Postmenopausal Women: A Randomized Acute Study

Abstract: OBJECTIVETo determine whether breaking up prolonged sitting with short bouts of standing or walking improves postprandial markers of cardiometabolic health in women at high risk of type 2 diabetes. RESEARCH DESIGN AND METHODSTwenty-two overweight/obese, dysglycemic, postmenopausal women (mean 6 SD age 66.6 6 4.7 years) each participated in two of the following treatments: prolonged, unbroken sitting (7.5 h) or prolonged sitting broken up with either standing or walking at a self-perceived light intensity (for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
242
4
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 241 publications
(292 citation statements)
references
References 33 publications
(38 reference statements)
24
242
4
6
Order By: Relevance
“…The outcome of the present study fits the emerging picture that breaking up sedentary behaviour by light-intensity activities may help to improve glucose homeostasis in groups, ranging from young lean normoglycaemic individuals [16] to overweight/obese normoglycaemic [13] and dysglycaemic [14] participants. Very recently, Dempsey et al showed that breaking up sitting time with brief bouts of light-intensity walking or resistance exercise attenuates postprandial glucose and insulin responses in type 2 diabetes [12].…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The outcome of the present study fits the emerging picture that breaking up sedentary behaviour by light-intensity activities may help to improve glucose homeostasis in groups, ranging from young lean normoglycaemic individuals [16] to overweight/obese normoglycaemic [13] and dysglycaemic [14] participants. Very recently, Dempsey et al showed that breaking up sitting time with brief bouts of light-intensity walking or resistance exercise attenuates postprandial glucose and insulin responses in type 2 diabetes [12].…”
Section: Discussionsupporting
confidence: 81%
“…3c), from 211 (44) min/day in the Sitting regimen to 118 (32) (Fig. 3d) Insulin resistance (HOMA2-IR) and plasma lipids Fasting insulin levels in the Exercise regimen were similar to those in the Sitting regimen (102 [14] vs 108 [13] pmol/l, respectively; p = 0.117). In contrast, compared with Sitting, Sit Less significantly (p = 0.001) reduced fasting insulin levels to 95 [14] pmol/l).…”
Section: Continuous Glucose Monitoringmentioning
confidence: 71%
See 3 more Smart Citations